2006
DOI: 10.1182/blood-2006-08-044990
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane receptor blockade improves the antiatherogenic effect of thromboxane A2 suppression in LDLR KO mice

Abstract: Suppression of thromboxane (Tx)A IntroductionAtherosclerosis is a complex and chronic inflammatory disease of the arterial wall influenced by diverse biochemical factors, including cytokines, chemokines, and growth factors. 1 One group of these mediators is represented by the prostanoids, a large family of bioactive lipids generating from arachidonic acid by the enzyme cyclooxygenase (COX). 2 The biosynthesis of prostanoids, specifically thromboxane A 2 (TxA 2 ) and prostacyclin (PGI 2 ), is grossly altered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Thromboxane A 2 reportedly plays a role in a variety of cardiovascular diseases, including myocardial infarction, cerebral vasospasm, hypertension, preeclampsia, and thrombotic disorders. 3,27,28 Accumulating findings demonstrated that ATP-sensitive K ϩ channels contribute to pathophysiological vasodilation during hypoxia, acidosis, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboxane A 2 reportedly plays a role in a variety of cardiovascular diseases, including myocardial infarction, cerebral vasospasm, hypertension, preeclampsia, and thrombotic disorders. 3,27,28 Accumulating findings demonstrated that ATP-sensitive K ϩ channels contribute to pathophysiological vasodilation during hypoxia, acidosis, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…335 A selective COX-1 inhibitor, SC560, and TP antagonist, BM-573, or a combination of both showed protection in atherosclerosis development, in LDLR-deficient mice on a high-fat diet. 336 These observations indicate that a combinatorial therapy simultaneously targeting atherosclerosis and thrombosis can be of great value. However, recent findings have associated NSAID action with thrombosis and hypertension.…”
Section: Within the Atheroma The Helper T-cells Can Polarize Into Thmentioning
confidence: 99%
“…Numerous studies have suggested the interest of disrupting the TXA 2 signaling pathway to reduce atherosclerosis, either by inhibiting TXA 2 production [58][59][60], blocking TP receptors [61][62][63] or combining a TXA 2 synthesis inhibitor and a TP receptor antagonist [64][65][66]. Pharmacological inhibition of TXA 2 biosynthesis with non-steroidal anti-inflammatory preferential COX-1 inhibitor [58], low-dose aspirin [60] or a more selective COX-1 inhibitor (SC560) [59,64] reduced atherosclerosis lesion size.…”
Section: Pharmacological Approachmentioning
confidence: 98%
“…Pharmacological inhibition of TXA 2 biosynthesis with non-steroidal anti-inflammatory preferential COX-1 inhibitor [58], low-dose aspirin [60] or a more selective COX-1 inhibitor (SC560) [59,64] reduced atherosclerosis lesion size. In ApoE −/− mice exposed to IH for 8 weeks, COX-1 inhibition by SC-560 during the last 4 weeks of IH exposure reduced the IH related progression of established atherosclerosis [8].…”
Section: Pharmacological Approachmentioning
confidence: 99%